Relationship between body composition and limb muscle power of taekwondo athletes - Aulya Safiyna Nuuril Anwari; Indra Himawan Susanto; Awang Firmansyah; Yetty Septiani Mustar (Sriwijaya Journal of Sport, 2025)
Research Problems: The kicking technique in taekwondo is predominantly utilized, necessitating significant leg muscle power to achieve optimal performance. Taekwondo is closely associated with weight categories in competitions. Body composition and leg muscle power are important factors in implementing the correct techniques for kicking and leg movements. Research Objectives: This study aims to determine the relationship between body composition and leg muscle power among East Java taekwondo athletes. Methods: The participants in this study included 51 East Java taekwondo athletes, comprising 27 male and 24 female athletes. Data were collected through body composition measurements using Bioelectrical Impedance Analysis (BIA) and the Countermovement Jump (CMJ) test to measure the leg muscle power of taekwondo athletes. This study employs a descriptive quantitative research design with a cross-sectional approach. Results: A significant relationship was found between body weight, height, Fat-Free Mass (FFM), Skeletal Muscular Muscle Mass (SMM), and Percent Body Fat (PBF) with leg muscle power and jump height, with a p-value <0.001. Conclusion: Body composition significantly influences leg muscle power, which in turn supports the performance of taekwondo athletes in jumps and kicks.